Digital Literacy Level and Information Source Evaluation Ability: A Case Study of Library and Information Science Students at Padang State University - Febrianti, Sherin; Rahmah, Elva (Darul Yasin Al Sys, 2026)
This study is motivated by the gap between the high intensity of digital technology use and the relatively limited critical evaluation skills of information sources among university students. Although students are often considered digital natives, they may still experience difficulties in assessing the credibility, accuracy, and reliability of information, particularly among students in the Library and Information Science Program at Universitas Negeri Padang. This study aims to describe students’ levels of digital literacy, their ability to evaluate information sources, and the relationship between these two aspects. A quantitative approach with a descriptive method was employed. The population consisted of 364 active students from the 2022–2025 cohorts, from which 85 respondents were selected using stratified random sampling based on the Slovin formula. Data were collected through a questionnaire consisting of 40 statements and analyzed using descriptive statistics. The findings indicate that students’ digital literacy was categorized as good, with a mean score of 4.00; information synthesis obtained the highest score, whereas information searching skills obtained the lowest score. Students’ ability to evaluate information sources was also categorized as good, with a mean score of 4.07; relevance was the highest-rated indicator, while authority was the lowest. These findings suggest that students generally demonstrate adequate digital literacy and information evaluation skills, although weaknesses remain in information searching techniques and in assessing the authority and purpose of sources. This study contributes to the literature on digital literacy and information literacy by providing empirical insight into the competencies of prospective information professionals. Practically, the findings imply the need to strengthen critical literacy education, develop curricula focused on information evaluation, and provide continuous training to enhance students’ capacity to assess digital information effectively. Keywords: Digital Literacy; Information Source Evaluation; Information Literacy; Library and Information Science Students; Critical Literacy